Nudity, Blood and Scopophilia. Disgust in Roman Polanski’s Macbeth (Itinera, 2024)
In 1971, only two years after the massacre of his family on behalf of Charles Manson and his “disciples”, Roman Polanski directed a controversial film adaptation of William Shakespeare’s Scottish tragedy produced by the Playboy tycoon Hugh Hefner. The resultof this peculiar combination of intents is a raw, often visually brutal film in which the concepts of evil and disgust overlap repeatedly in the form of uncanny images that the audience will hardly forget.The aim of this paper is to illustrate how Polanski uses and modifies the original Shakespearean material and the horror of his personal experience, with particular attention to nudity, blood and scopophilia, to evoke uneasiness and disgust. The analysis will focus on some specific choices that emphasize pivotal moments of the tragedy mostly through a process of over showing.
Keywords: Polanski, Macbeth, Nudity, Blood